Influence of Lithium Bromide on Electrical Properties in Bio-based Polymer Electrolytes - Fuzlin, Ahmad Faizrin; Sahraoui, Bouchta; Samsudin, Ahmad Salihin (UI Scholars Hub, 2020)
This research presents the influence of lithium bromide (LiBr) on the electrical properties of alginate in bio-based polymer electrolytes (BBPEs) system. Bio-based alginate was prepared using the solution casting technique with various LiBr compositions. The ionic conductivity and electrical properties of the prepared BBPEs samples were studied using electrical impedance spectroscopy over a frequency range of 50 Hz–1 MHz. A maximum ionic conductivity of 7.46 × 10−5 S cm-1 was obtained for a sample containing 15 wt. % lithium bromide-doped alginate BBPEs at ambient temperature (303 K). The electrical analysis revealed that the most conductive sample based on alginate-LiBr BBPEs has optimum dielectric constant and loss, which significantly increases as temperature increases. The dielectric properties show that all alginate-LiBr BBPEs are in non-Debye behavior conditions, where no single relaxation occurs in the present system.